(untitled) (International Journal of Environmental Sciences, 2025)
It is important to consider the impact of inadequate waste management on human health. In addition, it is important to consider the impact of poor waste management on the quality of the environment.The aim of this research is to formulate strategies to conserve and protect natural resources and control pollution, in the face of the environmental challenges facing all organisations. The creation of a database was an integral component of the production process for this paper, with the objective of comprehensively encompassing the multifaceted impact of environmental knowledge. The database has three parts. The first part is called "systems knowledge". The second part is called "action knowledge". The third part is called "effectiveness knowledge".It is evident that the database has been compiled from a variety of sources around the globe. The study demonstrates that effective waste management is inseparable from the management of both good waste management and community lifestyles. However, the challenges posed by waste management issues have proven to be substantial. Key constraints include the need for public awareness initiatives to minimise waste production at the individual, family and environmental levels.